2004
DOI: 10.4049/jimmunol.172.2.890
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of CCR2 during Initiation and Progression of Collagen-Induced Arthritis: Evidence for Regulatory Activity of CCR2+ T Cells

Abstract: Chemokines play an important role in the recruitment of leukocytes and have recently been shown to also attract regulatory T cells. Using blocking mAbs, we analyzed the role of the chemokine receptor CCR2 during initiation and progression of collagen-induced arthritis in mice. Blockade of CCR2 from days 0 to 15 markedly improved clinical signs of arthritis and histological scores measuring leukocyte infiltration, synovial hyperplasia, and bone and cartilage erosion. CCR2 blockade during disease initiation sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
141
1
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 37 publications
7
141
1
1
Order By: Relevance
“…Results of staining for CCR2 on monocytes and basophils are representative of at least 3 experiments. majority of CD4ϩ,CCR2ϩ T cells also stain positive for the regulatory T cell markers CD25 and CD103 and fulfill functional criteria of regulatory T cells in vitro (13).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Results of staining for CCR2 on monocytes and basophils are representative of at least 3 experiments. majority of CD4ϩ,CCR2ϩ T cells also stain positive for the regulatory T cell markers CD25 and CD103 and fulfill functional criteria of regulatory T cells in vitro (13).…”
Section: Resultsmentioning
confidence: 83%
“…We have previously shown that treatment with a blocking mono-clonal antibody (mAb) against CCR2, MC-21, administered at 500 g every third day, improves arthritis, when the treatment is started before the first immunization with collagen (13). In contrast, when the treatment is started later, a marked aggravation of arthritis occurs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of arthritis was evaluated using the following 2 parameters: synovial inflammation (0 ϭ normal, 1 ϭ focal inflammatory infiltrates, and 2 ϭ inflammatory infiltrate that dominates the cellular histology) and bone destruction (0 ϭ normal, 1 ϭ small areas of bone destruction, 2 ϭ widespread bone destruction), as described previously (32,33). Statistical analysis.…”
Section: Nanki Et Almentioning
confidence: 99%
“…In addition to the effects of the CCR2 null mutation in infection models, CCR2-deficient mice failed to recruit macrophages in a model of sterile peritoneal inflammation induced by thioglycollate [27][28][29][30][31]. Antibody blockade of CCR2 also prevented macrophage accumulation in thioglycollate peritonitis [32], but did not inhibit infiltration of inflamed joints by monocytes during progression of collagen-induced arthritis suggesting that under certain conditions of inflammation recruitment of macrophages may be independent of CCR2 [33].…”
Section: Introductionmentioning
confidence: 99%